2005
DOI: 10.1111/j.1600-0714.2005.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

The high prognostic value of the histologic grade at the deep invasive front of tongue squamous cell carcinoma

Abstract: This study found that a high IFG malignancy score had a high prognostic value for squamous cell carcinoma of the tongue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 39 publications
7
71
0
6
Order By: Relevance
“…The considerable variation in the histological aspect of this condition led to the development of a number of systems for the histological grading of malignancy. These systems were designed to allow for an interpretation of the aggressiveness of the tumor (1). In 1920, Broders (2) used cell pleomorphism and keratin production as parameters for the assessment of cell differentiation and the number of mitoses for the assessment of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The considerable variation in the histological aspect of this condition led to the development of a number of systems for the histological grading of malignancy. These systems were designed to allow for an interpretation of the aggressiveness of the tumor (1). In 1920, Broders (2) used cell pleomorphism and keratin production as parameters for the assessment of cell differentiation and the number of mitoses for the assessment of tumor growth.…”
Section: Introductionmentioning
confidence: 99%
“…Kurokawa et al (1) studied the relationship between the scores obtained using Bryne's method and the prognosis of patients with squamous cell carcinoma of the tongue. Results showed that patients with a score below 8 had a more positive prognosis, whereas those with a score of 11 or higher had a poorer prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…The most promising factor emerging from these studies seemed to be the depth of tumor infiltration. [14][15][16][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Even nowadays, many centers still rely on cutoff values of 4 or 5 mm of tumor depth for indication of elective neck treatment. With regard to the much more focused and precise histological staging of sentinel lymph nodes in contrast to nodes in neck dissection specimens, the aim of this study was to assess whether any of the formerly evaluated clinical or histologic factors in the primary tumors were still significantly predictive of occult disease in the context of SNB.…”
mentioning
confidence: 99%
“…El hallazgo de cáncer en los ganglios es el factor de riesgo para recurrencia, ya que disminuye la sobrevida de 50% a 15-30% en un periodo de 5 años (6). Varios estudios coinciden en que el hallazgo de cáncer en los ganglios regionales es el factor de riesgo para recurrencia (3)(4)(5)(6). Una serie grande publicada por Lam, con más de 600 sujetos con diagnóstico de cáncer de lengua, acumulados en 24 años, muestra que factores como: la presencia de ganglios cervicales comprometidos, la localización del cáncer en la base de la lengua y la edad avanzada, están relacionados con una menor tasa de sobrevida.…”
Section: Importancia De La Detección Temprana De Cáncerunclassified